The saddle maker's son - Irvin, Kelly (Irvin, Kelly. Amish of Bee County., 2018)
Rebekah Lantz feels imprisoned by circumstances she didn't create. Tobias Byler is haunted by regret. Can two young runaways from half a world away teach them the healing power of true family? Rebekah isn't like her sister, but the watchful gaze of her family and small, close-knit Amish community makes her feel as if she's been judged and found lacking. The men avoid her, and the women whisper behind her back. She simply longs for the same chance to be a wife and mother that her friends have. Tobias Byler only wants to escape feelings for a woman he knows he should never have allowed to get close to him. Moving with his family to isolated Bee County, Texas, seemed the best way to leave his mistakes behind. But even a move across the country can't erase the past that accompanies his every thought. A surprise encounter with two half-starved runaway children forces both Rebekah and Tobias to turn to each other to help a sister and brother who have traveled thousands of miles in search of lives of unfettered peace and joy. In doing so, Rebekah and Tobias discover the key to forgetting the past is the one that will open the door to love and the future they both seek.